The mystery of the man with the black beard - Cross, Gillian (Edinburgh: Barrington Stoke, 2014)
Annie's dad is a private investigator. She's used to mysterious things going on, but when a string of visitors come to her dad's office, it results in the most mysterious event of all - her dad has disappeared! Annie knows something is wrong and she enlists the help of her friends Matt and Ruth to follow a trail of very sticky clues
Keywords: Humorous stories